Influence of thrips prey species on the lifehistory and behaviour of Orius albidipennis (Reuter) (Heteroptera) - Fritzsche, M.; Tamo, Manuele (Wiley, 2000)
The effects of two diets, i.e., cowpea leaves plus Megalurothrips sjostedti larvae versus cowpea leaves alone, on nymphal development and mortality of Orius albidipennis were studied under controlled laboratory conditions in Benin, West Africa. Nymphal development was longer when O. albidipennis was fed with cowpea leaves only, compared to the diet complemented with M. sjostedti larvae (17.6 days versus 14.8, respectively). Nymphal mortality was very high (78.6%) if fed with cowpea leaves only, and still relatively high if the diet was complemented with thrips larvae (44.4%). In a separate study on the longevity and fecundity of O. albidipennis adult females feeding on M. sjostedti larvae, an average of 6.8 eggs per day (maximum 16 eggs) and a mean total fecundity of 61.1 eggs were observed. The females lived on average 13.5 days. Finally, observations on the predation by O. albidipennis adults on three different thrips species revealed that M. sjostedti larvae were killed at a lower rate than larvae of Ceratothripoides cameroni and Frankliniella schultzei. Higher predation rates were measured using unmated females and males than in mated females. However, the rate of first attack, measured as first larva attacked in dual‐choice assays, was higher for M. sjostedti when a F. schultzei larva was offered simultaneously, and not different when a C. cameroni or Sericothrips adolfifriderici larva was offered. The results of this study are discussed with regard to the lack of efficacy of O. albidipennis as biological control agent for M. sjostedti.